PENINGKATAN PENERIMAAN PAJAK PENGHASILAN MELALUI PELAKSANAAN EKSTENSIFIKASI PERPAJAKAN PADA KANTOR WILAYAH DIREKTORAT JENDERAL PAJAK ACEH - yunina, fitri (Universitas Teuku Umar, 2021)
This research purposes to analize and evaluate increasing effectivity of tax income by taxes extensification. Using secondary data by tax income data and number of tax payer that related to taxes extensification during period 2015 to 2019 in Regional Office Direktorat Jenderal Pajak Aceh Result showing that effectivity of tax extensification for increasing taxincome at Kanwil DJP Aceh still low with percentage about 35, 20%. This is because a lot of tax payer that had been registered not yet operate., Pembinaan for new tax payer not optimal, and klasification for business field not proper, example work finder that given non worker at classification business field when they registered, when they not having potention as tax payer. Keywords : Tax extensification and tax effectivity